2015
DOI: 10.1155/2015/649184
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Undiagnosed Hypertension in an Apparently Healthy Western Indian Population

Abstract: This epidemiological study was designed to evaluate the prevalence of undetected hypertension in an apparently healthy western Indian population having no history of major illness. 3629 individuals of ≥18 years of age were included in the study. Hypertension (HTN) was defined as systolic blood pressure (SBP) ≥ 140 mmHg or diastolic blood pressure (DBP) ≥ 90 mmHg and prehypertension (PHTN) as SBP ≥ 120-139 mmHg or DBP ≥ 80-89 mmHg, but without HTN. The prevalence of undiagnosed HTN in the total population was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 16 publications
5
25
3
3
Order By: Relevance
“…In developing countries, most people with raised blood pressure are unaware of their condition [6]. A holistic strategy to reduce complications and mortality due to hypertension must include preventive measures and early detection among others [7]. This is the role of screening and it had been recommended by the World health Organization that "'early detection is the Key' for prevention and treatment of high blood pressure and that all adults should know their blood pressure" [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, most people with raised blood pressure are unaware of their condition [6]. A holistic strategy to reduce complications and mortality due to hypertension must include preventive measures and early detection among others [7]. This is the role of screening and it had been recommended by the World health Organization that "'early detection is the Key' for prevention and treatment of high blood pressure and that all adults should know their blood pressure" [1].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of hypertension and associated factors in older adults in South Africa, it was found that hypertension was more prevalent (77.3%) among older adults aged 50 years and more in South Africa and it is prevalent in Rwanda at a rate of 41% and 36.6% for men and women respectively [8]. Since the blood pressure tends to rise as individual becomes older, high blood pressure is frequently found in old people compared to other age group [7] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out among 10,175 adults aged ≥20 years in slums of Kolkata reported the prevalence of hypertension as 42% and prevalence was higher in men, above 60 years age, in minority community, in those with a higher household income, and among tobacco users [19]. An epidemiological study carried out among 3629 adults between younger and older two age groups in western Indian population showed that hypertension prevalence differs in two different age groups 11% in younger (≤40 years)and 40% in older age groups (>40years) [20].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Because hypertension causes extensive cardiovascular morbidity and mortality and increased cost of health care; various modalities of preventive measures are being promoted. Studies on Meditation have shown that it helps in changing lifestyle, behavior and outlook towards life and may be effective in management of hypertension as a primary preventive strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Negative emotions such as anger, hatred, ill will, animosity may accelerate blood pressure and person may develop ischaemic heart disease, myocardial infarction and stroke. [2][3][4][5][6][7][8][9] At hormonal level mental stress increases release of catecholamine, corticoids and thyroxine which are strongly associated with rise in blood pressure both systolic and diastolic. 6,7,10 Cardiovascular diseases carry highest mortality among all cause deaths (23%).…”
Section: Introductionmentioning
confidence: 99%